Otimização de parâmetros no tratamento de efluentes têxteis através de processos oxidativos avançados - Toral, José Augusto de Oliveira (2013)
This study aims to analyze the efficiency of heterogeneous catalytic photooxidation treatment on textile effluents arising from dyeing processes. Applying a full factorial design, the performance parameters pH, reaction processing time, catalyst mass (TiO2) and UV radiation power were measured in order to determine their influence on the percentage of effluent discoloration, allowing to identify those who have greater significance to the analytical response. For that, the effluent’s characterization was performed shortly after his collect on an industrial laundry located in Maringá – PR, and then, it was applied to the photocatalytic degradation treatment in an UV reactor, built in UTFPR – Campus Apucarana. Thus, using tools for the statistical interpretation of the obtained results, it was possible to generate and correlate data in order to determine the optimum parameters of the process. To the variables studied in this work, the results of statistical analyzes identified significance only on effluent’s initial pH.